A TEXTUAL PROBLEM IN EURIPIDES - White, Heather (Myrtia, 2004)
The difficulties which are presented to us by these lines have been clearly set out by Prof. E. Calderón in his masterly edition1. His argumentation has enabled me, I hope, to solve the problem.